Political Identity In The Perspective Of The Christian Faith: Welcome To The Future - Juan Carlos (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Identity politics is a political tactic in which people or groups organize themselves based on certain traits such as religion, culture, race, gender, sexual orientation, or even hobbies. This can happen due to discrimination or injustice in society that makes the person or group feel the need to form a similar group for support and protection. In the context of society, identity politics can appear in various forms such as feminist movements, anti-racism movements, or LGBT movements. However, we must also beware of the dangers of identity politics that can divide society and create conflicts between different groups. The basis of Christian belief also teaches us to live in peace and harmony with fellow human beings. We are taught to forgive and give others a second chance. In the context of identity politics, these values and principles can help us build inclusive and peaceful societies where every individual feels valued and accepted.